PENGARUH APLIKASI PUPUK ROCK PHOSPHATE DAN MIKROBA PELARUT FOSFAT TERHADAP PERTUMBUHAN DAN KADAR HARA P BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) - Ingrid Ovie Yosephine; Nicolas Ferreira; Dina Arfianti Saragih (Institut Teknologi Sawit Indonesia, 2019)
One way to produce good seeds is from fertilization factors, both artificial fertilizers or biological fertilizers. Palm oil growing media is soil in which there are several nutrients needed by plants, one of which is Phosphor (P). The role of P in plants is important for cell growth, formation of fine roots and root hairs, strengthening the stem stands. However, there are still many P nutrients that are bound in the soil so with that one effort to overcome the low phosphate available in the soil is by utilizing a group of microorganisms. Microorganisms and organic matter, each of which can produce organic acids that chew metal in the soil so that phosphate becomes available to plants.